Effective Utilization of Fly Ash for Vermicompost Production by Employing Eisenia fetida - Selvakumar Muniraj, Logeswari Ravi, Harisankar Ganesh, Murugavel Sethuraman , Vasanthy Muthunarayanan (Nature Environment and Pollution Technology, 2020)
Thermal Power plants cater the energy needs in many of the countries across the globe, but they indeed pose health hazard to the atmosphere by the release of pollutants such as fly ash, particulate matter, dust, smoke-laden with gaseous pollutants etc., As it is mandatory to meet the energy demand of the increasing population, it is also important to manage the waste produced as the result of these industries. Though there exist various methodologies to manage the waste, vermicomposting is one of the cost-effective and simple techniques available to manage many of the solid waste emanated from different industries. Hence, this study was made to manage the fly ash waste by vermicomposting technique after the addition of carbon substrate namely, the cow dung in different rations such as 1:1, 1:4, 4:1, 2:3 and 3:2. The organism selected for the research was Eisenia fetida. The number of days for the process was about 60 days. The physico-chemical changes were monitored throughout the study period at regular intervals. The bacterial strains were isolated from the end product, namely the vermicast or vermicompost. Their enzyme activity was also checked and the end product was characterized using FTIR and XRD. Of the different proportions, 1:4 was found to be a suitable proportion in terms of the parameters checked.